Upaya Meningkatkan Hasil Belajar IPS Materi Berbagai Pekerjaan Menggunakan Model Pembelajaran Problem Based Learning Kelas IV SDN 4 Lahat Selatan - Robili; Lia Rismawati (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This classroom action research aims to improve the learning outcomes of fourth grade students of SD Negeri 4 Lahat Selatan in the subject of Social Studies on the material "Various Jobs" through the Problem Based Learning (PBL) learning model. The subjects of the study were 15 students. The study was conducted in three stages, namely initial learning (pre-cycle), cycle I, and cycle II. In the initial learning, only 40% of students achieved the Minimum Completion Criteria (KKM) ? 65, while the other 60% had not completed it. After improvements were made to learning in cycle I, the percentage of completion increased to 67%, but had not reached the target for learning success. Further improvements were made in cycle II, by correcting deficiencies in cycle I, such as adding learning media. As a result, all students (100%) achieved scores above the KKM. The results of the study indicate that the application of the right Problem Based Learning learning model can effectively improve student learning outcomes.